HUBUNGAN BERAT BADAN LAHIR RENDAH DENGAN KEMAMPUAN BAHASA EKSPRESIF ANAK UMUR DUA SAMPAI TIGA TAHUN DI DESA TUKO PURWODADI - Amelia, Salsabilla Nor; Syah Fitri, Anisyah Dewi (Medical Journal of Nusantara, 2023)
Background: Babies with LBW are at risk for many health problems such as falling ill in the first six days of life or having an infection, and can also suffer long-term problems such as delayed motor and social development or learning disabilities (Manurung & Helda, 2021). Expressive language is the ability to communicate symbolically both visually and auditory with the aim of helping children to be able to express their needs, wants, and feelings verbally. (Fatwikiningsih, 2014). Objective: This study aims to determine wheter there is a correlation between low birth weight and expressivelanguage skills children aged two to three years in Desa Tuko Purwodadi. Methods: This research is a quantitative research . The research design used in this research is descriptive correlational with a cross sectional approach. The sample size used was 28 respondents. The collected data was tested using Spearman Rank. Research Results: The Sprearman Rank test results obtained sig. 0.033 where the significance value is less than 0.05 with a correlation coefficient of 0.404. So that Ha is accepted, that is, there is a relationship between LBW and expressive language skills of moderate strength. Conclusion: There is correlation between low birth weight and expressivelanguage skills children aged two to three years in Desa Tuko Purwodadi